Ethical Leadership in Medical Laboratory Technology (MLT) Education and Management - Rinda Lestari; Suryani Suryani; Marisa Marisa (Civiliza Publishing, Indonesia., 2026)
This study is grounded in the importance of ethical leadership in the management of Medical Laboratory Technology (MLT) laboratories, which play a pivotal role in ensuring service quality, workplace safety, and professional accountability within educational and healthcare settings. The study aims to integrate the concept of ethical leadership with moral philosophy to understand their combined role in supporting effective and sustainable laboratory management practices. A systematic literature review was conducted, analyzing relevant sources concerning ethical leadership, moral philosophy, and health laboratory management. The findings indicate that moral philosophical principles such as deontology, utilitarianism, virtue ethics, and the ethics of care serve as the normative foundation for decision-making by laboratory leaders. Ethical leadership acts as a bridge between moral values ​​and operational practices by fostering a safety culture, enhancing personnel accountability, and maintaining sustainable service quality. Furthermore, ethics education and leadership development are deemed essential for shaping the professional character of laboratory and healthcare personnel, thereby directly impacting the quality of diagnostic results and patient safety. In conclusion, MLT laboratory leadership should be viewed as a moral practice rooted in robust ethical principles and manifested through ethical policies and organizational culture, thereby supporting the sustainability of service quality and safety in laboratory management.